2018
DOI: 10.4103/0366-6999.247194
|View full text |Cite
|
Sign up to set email alerts
|

New-Onset Geriatric Epilepsy in China

Abstract: Background:Few studies have been published on new-onset geriatric epilepsy especially in older Chinese people. This study was to have a comprehensive understanding of new-onset geriatric epilepsy and find a more reasonable diagnosis and management of epilepsy in older people.Methods:One hundred and three patients with onset age 60 years and older were admitted between January 2008 and December 2016. Electronic medical records were reviewed to collect information.Results:There were 103 older patients with new-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 21 publications
0
7
1
Order By: Relevance
“…In one Chinese cohort of 103 patients with geriatric new onset epilepsy (onset at age > 60 years), the most common cause was autoimmune (41.7%). 14 A similar theme is seen in new onset refractory SE (NORSE), in which autoimmune mechanisms such as AIE are believed to be the most common cause. 15,16…”
Section: Prevalencementioning
confidence: 87%
“…In one Chinese cohort of 103 patients with geriatric new onset epilepsy (onset at age > 60 years), the most common cause was autoimmune (41.7%). 14 A similar theme is seen in new onset refractory SE (NORSE), in which autoimmune mechanisms such as AIE are believed to be the most common cause. 15,16…”
Section: Prevalencementioning
confidence: 87%
“…In addition, both systemic and CNS inflammation can precipitate epileptic seizures [12]. In such intricate scenario, AEs have recently provided a peculiar model of seizures related to aberrant adaptive immunity [14], and are supposed to account for a large proportion (reportedly, up to 40%) of late-onset epilepsy cases [15].…”
Section: Discussionmentioning
confidence: 99%
“…This predominance of focal-onset seizures has been reported previously in several studies. 4,6,10,11 However, Kuate-Tegueu et al 5 reported as far as they are concerned in Cameroon a predominance of generalized tonic-clonic seizures (44%).The high prevalence of focal brain lesions in the elderly explains this predominance of focal-onset seizures in these persons.…”
Section: Discussionmentioning
confidence: 99%
“…Maiga et al 4 in their study reported a proportion of epilepsies without a defined etiology of 18%, but these authors do not specify if the workup was complete or no in their patients. Chen et al 10 reported as far as they are concerned autoimmune encephalitis as the most common identified causes followed by cerebrovascular disease. The same authors report a proportion of epilepsies without a defined etiology of 21.4%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation